Carrier Transfer and Capture Kinetics of the TiO2/Ag2V4O11 Photocatalyst - Yun Zhou; Qiujie Ding; Yuan Wang; Xiaoping OuYang; Lixin Liu; Junyu Li; Bing Wang (Nanomaterials, 2020)
In this paper, TiO2/Ag2V4O11 nanoheterojunctions have been synthesized by hydrothermal methods, which show enhanced photocatalytic activity compared to TiO2 under visible light. Moreover, the TiO2/Ag2V4O11 nanoheterojunction with set molar ratio of 2:1, referred to as TA2, show the highest visible light photocatalytic activity, which could decompose about 100% RhB molecules within 80 min of irradiation with visible light. Specially, the time-resolved photoluminescence spectrum of TA2 demonstrates that the free exciton recombination occurs in approximately 1.7 ns, and the time scale for Shockley–Read–Hall recombination of photogenerated electrons and holes is prolonged to 6.84 ns. The prolonged timescale of TA2 compared to TiO2 and Ag2V4O11 can be attributed to the carrier separation between nanojunctions and the carrier capture by interfacial defects. Furthermore, the enhanced photocatalytic activity of TiO2/Ag2V4O11 nanoheterojunctions also benefits from the synergistic effect of the broadened absorption region, higher photocarrier generation, longer carrier lifetime, and quicker collection dynamics.